SMART DIGITAL LEARNING: A SNAPSHOT OF WEB-BASED LEARNING MANAGEMENT SYSTEM - Audi Yundayani; Fiki Alghadari; Bejo Sutrisno (Journal of Learning and Technology, 2022)
This study aims to identify the use of Smart Digital Learning (SDL) as an alternative to web-based learning management systems (WLMS), web-based presentations, and web-based modules. The research approach used in this study is the Research and Development method. The data analysis technique uses a descriptive calculation of proportions derived from student response data, expert tests and media tests on the products produced. A total of 72 students from three different classes were included as research respondents. The results of this study found that SDL can facilitate independent learning, arouse student interest in learning, present multimodal texts, can be designed based on learning needs, can be used as a website portfolio, interaction between users must be increased, and requires a stable internet connection.